P347 Sarcopenia is a poor prognostic factor for endoscopic outcomes in patients with Crohn's disease. (21st January 2022) - Grova, M; Crispino, F; Maida, M; Vitello, A; Tesè, L; Rizzuto, G; Casà, A; Renna, S; Macaluso, F S; Orlando, A
Abstract: Background: Sarcopenia is defined as depletion in lean muscle mass with a loss of muscle strength and has been associated with increased morbidity and mortality in chronic diseases. Despite the risks and potential consequences of low lean muscle mass in patients with Crohn's disease (CD), the impact of sarcopenia has been poorly evaluated. Therefore, the aim of our study was to assess the role of sarcopenia in predicting clinical and endoscopic outcomes in a cohort of CD patients. Methods: Consecutive CD patients who started biologics between, 2015 and, 2020 and who underwent abdominal magnetic resonance imaging (MRI) within, 6 months from the beginning of the treatment were enrolled. Sarcopenia was defined as sex-specific total psoas area index (TPAI), measured at the, 3 rd lumbar vertebra level, below the, 25 th percentile. Multivariate analysis was used to evaluate whether sarcopenia could predict steroid-free clinical remission (Harvey-Bradshaw Index [HBI] <5 and no steroid treatment) and endoscopic response (Simple Endoscopic Score for Crohn's disease [SES-CD] ≤2 or SES-CD ≤2 and Rutgeerts score i0-i1) after, 52 weeks of treatment. Results: 358 patients were included. Sarcopenic patients were older (p = 0.001), with lower body mass index (BMI) (p = 0.001) and higher Charlson Comorbidity Index (p = 0.02). Furthermore, sarcopenia was associated with a lower rate of endoscopic response (p = 0.014) and a lower SES-CD and Rutgeerts score after, 52 weeks of treatment (p = 0.008; p = 0.001). In multivariate analysis, sarcopenia was an independent predictor of absence of endoscopic response (odds ratio [OR] = 2.8;, 95% confidence interval (95% CI), 1.1–7.5; p = 0.02), along with smoking (OR = 2.39;, 95% CI, 1.05–5.44; p = 0.038) and perianal disease (OR = 2.69;, 95% CI, 1.19–6.08; p = 0.017). Sarcopenia was not associated with steroid-free clinical remission. Conclusion: This is the first study demonstrating that sarcopenia is a poor prognostic factor for endoscopic response in CD patients. These results suggest that, in the future, screening for sarcopenia on routine abdominal MRI could be used in clinical practice for better management of CD patients in need of biological therapy. Further studies with a larger sample size and a validation cohort are needed to confirm our data.